Middle Ear Metastases as the Initial Presentation of Breast Cancer Progression - Tzu-Chien Lin; Ya-Chun Hsu; Hui-Wen Chen; Wei-Pang Chung* (Journal of Cancer Research and Practice)
Breast cancer (BC) is the most prevalent malignancy in women, and most of their deaths from BC are caused by metastases. The bone, liver, lungs, and skin are the most frequently involved organs in metastases. We report a rare case of middle ear metastasis from BC in a 67-year-old woman. The patient had a curative modified radical mastectomy for her right BC 24 years ago and was treated with letrozole as a first-line therapy for the recurrent disease since 2016. After more than 5.5 years of treatment, computed tomography revealed otitis media with mastoiditis, and a granular tumor was found in the attic space and mesotympanum during the operation with the initial symptom of decreased left ear hearing. The mass was incompletely removed, and a biopsy eventually confirmed metastatic BC. There are very few case reports in the literature. Our case highlights the importance of surgical biopsy in differentiating middle ear neoplastic lesions.